Этиопатогенетические, психопатогенетические и клинические аспекты когнитивных нарушений при сахарном диабете 2-го типа = Etiopathogenic, psychopathogenetic and clinical aspects of cognitive disorders in type 2 diabetes - Tkachenko, O. V. (Journal of Education, Health and Sport, 2015)
Tkachenko О. V. Этиопатогенетические, психопатогенетические и клинические аспекты когнитивных нарушений при сахарном диабете 2-го типа = Etiopathogenic, psychopathogenetic and clinical aspects of cognitive disorders in type 2 diabetes. Journal of Education, Health and Sport. 2015;5(11):279-288. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.34006 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2811%29%3A279-288 https://pbn.nauka.gov.pl/works/670229 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.09.2015. Revised 25.10.2015. Accepted: 10.11.2015. Этиопатогенетические, психопатогенетические и клинические аспекты когнитивных нарушений при сахарном диабете 2-го типа ETIOPATHOGENIC, PSYCHOPATHOGENETIC AND CLINICAL ASPECTS OF COGNITIVE DISORDERS IN TYPE 2 DIABETES О. В. Ткаченко О. V. Tkachenko Запорожская медицинская академия последипломного образования Министерства здравоохранения Украины Medical Academy for Post-Diploma Training of Doctors of the Ministry of Health care of Ukraine, Zaporozhe Summary Etiopathogenetic, psychopathogenetic and clinical aspects of cognitive impairments in type 2 diabetes patients have been analyzed and systematized. Etiopathogenetic and psychopathologic classification of cognitive disorders in the group under study is presented. Comorbid cognitive mental disorders for which cognitive impairment is a factor of amplification are detached. Morphological phenomena associated with cognitive insufficiency in the patients under study has been marked. The main tactics for cognitive insufficiency prevention and therapy in type 2 diabetes patients are considered. Key words: type 2 diabetes, cognitive impairment, mental pathology. Реферат В статье проанализированы и систематизированы этиопатогенетические, психопатогенетические и клинические аспекты когнитивных нарушений при СД 2-го типа. Приведена этиопатогенетическая и психопатологическая классификация когнитивных нарушений при СД 2-го типа. Рассмотрены коморбидные когнитивным психические расстройства, для которых когнитивные нарушения выступают фактором амплификации. Выделены ассоциированные с когнитивной недостаточностью морфологические феномены у пациентов с СД 2-го типа. Рассмотрены основные тактики профилактики и терапии когнитивной недостаточностью у пациентов с СД 2-го типа. Ключевые слова: сахарный диабет 2-го типа, когнитивные нарушения, психическая патология.